A vulnerability index formulation for the seismic vulnerability assessment of vernacular architecture - Ortega Heras, Javier (2019)
The valorization and preservation of vernacular architecture, as well as traditional construction techniques and materials, is a key-element for cultural identity. Conservation efforts are often mainly focused on historical constructions and monuments. Furthermore, more detailed and sophisticated seismic vulnerability assessment approaches typically used for monumental buildings require time, cost and resources that are not commonly assigned to the study of vernacular architecture. Earthquakes come unexpectedly, endangering in-use vernacular architecture and the population who inhabits it. That is why simplified methods for the seismic vulnerability assessment of vernacular architecture are of paramount importance. The present paper presents a new formulation for the vulnerability index method particularly adapted to the characteristics of vernacular architecture: Seismic Vulnerability Index for Vernacular Architecture (SVIVA). The vulnerability index method has been used extensively in the literature using different formulations that were always defined based on empirical knowledge acquired through post-earthquake damage observation and expert judgment. The SVIVA formulation is developed by means of an analytical process instead of the traditional empirical approach. The process included an extensive numerical modeling campaign that allows adapting the method to the characteristics of vernacular architecture by gaining a deeper quantitative knowledge on their seismic behavior.